The EC internal market: An "economic United States" of Europe - Amy Skolnik (Bank of Finland, 1988)
In 1985, the EC Commission set about creating an internal market which would allow for the free flow of goods, services, labor, and cap; tal between all member states. Si nce then, concrete progress in opening markets and removing barriers has been made in the areas of financial services, procurement methods, transportation, and standards. However, there are a few fundamental obstacles that will prevent the EC from attaining its final g~als. These include the issues of taxation, open borders, lack of a single monetary system, and above all, national interest. Member states greatly fear the 10ss of their independent policy-making power. In contrast to the UoS., with its vast single market, the EC nations have many cultures, languages, and customs; something that is not likely to change. It is these factors that will ultimately prevent full cooperation and complete integration within the European Community. This paper analyzes the main areas of progress as well as the major problems of the Internal Market and focuses on the proposal that the Internal Market will create an 'United Economic Unit' comparable to that of the United States.
URN:NBN:fi:bof-201807301746
Keywords: 330